Islamic Religious Teachers Innovation in Improving Students Learning Outcomes During Covid-19 Pandemic - Sagaf S. Pettalongi; Abbas Abbas; Sitti Hasnah (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2022)
The purpose of this study was to determine the learning innovation of Islamic Religious Education Teachers in Improving Student Learning Outcomes during the Covid-19 Pandemic at SMP Negeri 1 Sirenja, Donggala Regency. This study uses a qualitative method with a descriptive approach. Data collection was done by using observation, interview, and documentation techniques. Data analysis uses data reduction, data presentation, and concluding. The results showed that the innovation used by the teacher in the learning process was the implementation of online learning. The media used in online learning is by utilizing WhatsApp, Google Classroom, or Zoom media. Barriers faced by teachers in carrying out learning innovations during the COVID-19 pandemic are limited facilities, internet quotas, and networks. The results achieved from the learning innovations of Islamic religious education teachers during the COVID-19 pandemic did not show significant educational developments. This fact can be seen from the results of students' scores, which have decreased compared to learning outcomes before the COVID-19 pandemic. The implication of this research is that the learning innovation of Islamic religious education teachers in improving student learning outcomes during the COVID-19 pandemic at SMP Negeri 1 Sirenja district has been carried out by teachers.